Produção de biofilme a partir do soro de leite - Marquez, Anna Luiza Bergheme (2023)
In the current environmental crisis, the concern with the impacts of plastics due to their accelerated speed of production and consumption has generated great interest in the development of biofilms as an alternative to synthetic plastics. Considering the large substantial amount of whey occasionally discarded annually in Brazil as industrial waste, it generates a serious problem due to its high organic load when disposed without proper treatment in the environment. The aim of this study was to produce biodegradable films from whey protein concentrate and to evaluate its biodegradability and future potential as packaging. The procedure used to reduce the discarded volume of the dairy industry by-product was the cryoconcentration, with 87% volume reduction. Films were prepared from whey, pectin, polylactic acid with glycerol as plasticizer using the casting methodology. The films generated presented whitish colors and the total biodegradability of the films was verified in seven days. The mechanical tests showed a low tensile strength (0.04 to 0.91 kPa). It is observed that the biofilms produced demonstrated the possibility of using dairy waste for their production, containing interesting characteristics for the development of possible sustainable